THE EFFECT OF USING FLY ASH AS A CEMENT SUBSTITUTE ON THE QUALITY OF NICKEL SLAG-BASED PAVING BLOCKS - Soleman, Sadli; Sultan, Mufti Amir; Kusnadi; Marsaoly, Nurmaiyasa (International Journal of Research -GRANTHAALAYAH, 2025)
The Rum Steam Power Plant (PLTU) uses coal as an energy source. The waste produced from this process is in the form of solid waste with an amount of ±5% of the total waste. This solid waste is in the form of bottom ash and fly ash with a content of 80-90% in the form of bottom ash and the remaining 10-20% in the form of fly ash. Paving blocks are an important element in urban infrastructure, used for roads, sidewalks and other public areas. In recent years, attention to sustainability and the use of environmentally friendly materials has increased. This research will focus on analyzing the interaction of these two materials in paving block mixtures, with the aim of producing construction materials that are more efficient and environmentally friendly. The research results show that the substitution of cement with fly ash in paving blocks made from nickel slag has a significant effect on the mechanical and physical characteristics. The use of fly ash up to 20% shows relatively good results with a reduction in compressive strength and density that is not too significant, while the proportion of 30% shows a more drastic reduction. Therefore, it is recommended to use a maximum proportion of 20% fly ash as a cement substitute to achieve a balance between strength and sustainability.